112k views
4 votes
If f(x) = x^2 - 2x and g(x) = 6x + 4, for which value of x does (f + g)(x) = 0

2 Answers

3 votes

So for this, we will be adding f(x) and g(x) together and setting (f + g)(x) to 0 as such:


x^2-2x+6x+4=0

Firstly, combine like terms:


x^2+4x+4=0

Next, the left side of the equation is a perfect square. Factor it:


(x+2)^2=0

Next, square root both sides:


x+2=0

Lastly, subtract 2 on both sides and your answer will be
x=-2

User Ahmed Boutaraa
by
5.0k points
2 votes

(f + g)(x) = 0

x^2 - 2x + 6x + 4 = 0

x^2 + 4x + 4 = 0

(x + 2)^2 = 0

x + 2 = 0

x = -2

User Hippiehunter
by
5.1k points